Ph̄æn kānlongthun Čhangwat Čhanthaburī : sarup samrap phūb̨̄orihān (B̨̄orisat Sōsiʻō-ʻēkkhōnōmik Kh̨̄onsant̄æn čhamkat, 1994)
Investment plans for Chanthaburi Province, Thailand, summarized for province administrators.